EVALUATION OF ANTIOXIDANT PROPERTIES OF POLY HERBAL SIDDHA PREPARATION KARISALAI KARPA CHOORANAM - L, Juliet; S, Sivakkumar (International Journal of Ayurveda and Pharma Research, 2018)
In recent years, there has been a great deal of attention toward the field of free radical chemistry. Free radicals reactive oxygen species and reactive nitrogen species are generated by our body by various endogenous systems, exposure to different physiochemical conditions or pathological states. A balance between free radicals and antioxidants is necessary for proper physiological function. If free radicals overwhelm the body's ability to regulate them, a condition known as oxidative stress ensues. Free radicals thus adversely alter lipids, proteins, DNA and trigger a number of human diseases. Hence the researchers are searching a potent antioxidant drug from natural resource. In ancient time it has been clearly mentioned in Siddha system of medicine as Kaaya Karpam Therapy (Rejuvenation). Karisalai Karpa Chooranam (KKC) is a powerful poly herbal Siddha preparation mentioned in ancient Siddha literature. This medicine is indicated for Paandu (Anaemia), Kaamalai (Jaundice), Kalleral veekkam (Hepatomegaly), Sobai (Generalized edema), Skin diseases and helps to enhance the immune system. It is a powerful rejuvenating medicine in siddha system and used as a Kaayakalpam. This study is aimed to screen the antioxidant effect of KKC. In this study DPPH, Nitric Oxide and ABTS radical scavenging studies were performed. The results of this study shows that the percentages of inhibition in DPPH, Nitric Oxide and ABTS radical scavenging studies are 48.4 % (standard drug Ascorbic acid -78.64%), 50.7 % (Gallic acid – 86.2%) and 60 % (Gallic acid – 91.16%) respectively and thus, our findings provide evidence that KKC could be a potential source of natural antioxidant and it may be used as rejuvenating medicine for vast therapeutic effects, gives a powerful body, mind and soul with long-lasting life.